PERANCANGAN APLIKASI COMPUTER BASED TEST (CBT) TRY OUT UJI KOMPETENSI REKAM MEDIS BERBASIS WEB - Rizer Fahlepi; Wen Via Trisna (LPPM Universitas Awal Bros, 2026)
The use of Information and Communication Technology (ICT) in education has become an essential necessity in the era of globalization, including in the implementation of try-out examinations to prepare students for competency tests. The implementation of try-outs using the Paper-Based Test (PBT) method still faces several challenges, such as high operational costs, the risk of cheating, lengthy result-processing times, and increased paper usage that negatively impacts the environment. Therefore, this study aims to design a web-based Computer-Based Test (CBT) system for medical record competency test try-outs to support a more effective, efficient, flexible, and secure evaluation process. The method used in this study is the waterfall method, which consists of literature study, requirements analysis, system design, implementation, and system testing stages. The results of this study indicate that the web-based CBT application for medical record competency test try-outs was successfully developed and is capable of meeting students’ needs in conducting examination simulations in a more practical and structured manner. The designed system also provides convenience in question management, test implementation, and rapid and accurate result processing. Thus, the design of this web-based CBT system can serve as an alternative solution to improve students’ readiness in facing medical record competency examinations more optimally.